2004
DOI: 10.2214/ajr.183.3.1830801
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Measurement of the Abdominal Esophagus Length in Infancy: A Diagnostic Tool for Gastroesophageal Reflux

Abstract: Sonographic measurement of the abdominal esophagus length is highly diagnostic for GER in neonates and infants. In neonates, it can also indicate GER severity. Hiatal hernia is associated with a significantly shorter abdominal esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
5
28
0
1
Order By: Relevance
“…Other studies confirmed their findings [12,32,33]. In our study, although the IAEL did not significantly correlate with the severity of reflux in BS, we found that the IAEL was shorter in normal comparing with mild and moderate BS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Other studies confirmed their findings [12,32,33]. In our study, although the IAEL did not significantly correlate with the severity of reflux in BS, we found that the IAEL was shorter in normal comparing with mild and moderate BS.…”
Section: Discussionsupporting
confidence: 86%
“…hiatus hernia, malrotation) [8] along with the valuable experiences that practitioners have acquired through the years since the 1980s, ultrasonography (US) has been used as an alternative to BS in the diagnosis of GERD [9]. Esophageal US has been described as a noninvasive, readily available, repeatable, cheap, and fast technique that could be commonly used in the diagnosis and follow-up of young children with GERD [10][11][12][13][14][15]. Comparative studies of transabdominal US and BS demonstrated that US presents a higher sensitivity in the diagnosis of GERD [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…(14) Bir başka çalışmada ise, sonografik olarak abdominal özefagus boyu ölçümünün, GÖR tanısı konulmasında %94 oranında sensitiviteye sahip olduğunu gösterilmişdir. (15). Yenidoğanlarda GÖR'nün ilk bir ay içinde oldukça sık rastlandığı, fakat bu ay içindeki reflü-lerin daha çok nonasidik reflüler olduğu, çünkü anne sütünün asidik mide sıvısını tamponladığı ve bu nedenle de GÖR tanısında pH impedans ölçümünün daha anlamlı olduğunu bildirilmektedir (16).…”
Section: Discussionunclassified
“…Some studies have shown that a short lower portion of the thoracic esophagus can be visualized by transabdominal sonography performed through the window of the liver. [13][14][15] Zhu et al 16 suggested that despite its limitations, transthoracic sonography is an alternative for visualizing the thoracic esophagus in adults. In this study, we could not clearly show the thoracic esophagus in all of the children.…”
Section: Discussionmentioning
confidence: 99%